Soft Skill Competencies, Hard Skill Competencies, and Intention to Become Entrepreneur of Vocational Graduates - Riyanti, Benedicta Prihatin Dwi; Sandroto, Christine Winstinindah; Warmiyati D.W, M. Tri (Universitas Prasetiya Mulya, 2016)
This study aimed to determine the effect of soft skill competencies and hard skill competencies to the intention to become entrepreneur in the vocational school graduates. Hard skill entrepreneurial competencies are competencies that are needed to running business. Meanwhile for soft skill competencies are competencies related to aspects of personality and cognitive style. Population in this research is vocational graduates in Jakarta and Jogjakarta. The sampling technique used isincidental sampling. We used measuring instruments as follow: the intention to become entrepreneur of Shapero & Sokol (in Riyanti, 2009). soft skill competencies of Spencer & Spencer (1993) and hard skill competencies of Chou. Shen. Hsiou & Chen. 2010). The regression analysis of the 258 respondents showed significant effect of soft skill competencies (initiative. self-confidence and assertiveness) to the intention to become entrepreneur in the vocational school graduates. There are significant effect hard skill competencies (human resources capability competency and production capability competency) to the intention to be entrepreneur. Based on the results. we suggested that the learning process should be more emphasis on direct practice so that more competencies can be formed on vocational school graduates.